Physics of freezing under electromagnetic conditions: a review - LeBail, Alain; Jha, Piyush Kumar; Xanthakis, Epameinondas; Havet, Michel (My University, 2019)
Phase change in biological tissues may be affected by electric field, magnetic field and electromagnetic waves. This presentation proposes a review based on existing literature as well as some very recent results on freezing under static electric field and microwave conditions. The fundamentals of thermodynamics associated to freezing will be reminded. The interaction between water, water crystallization and electro-magnetic disturbances will be highlighted and different assumptions will be proposed. A review of existing results showed that for example the supercooling was decreased with increasing electromagnetic waves power level whereas the theory predicts the opposite. Besides, the theory supporting water freezing under static electric field matches well with the experimental results. A controversy exists about the possible impact of magnetic field (static and oscillating); this point will be tackled and discussed based on electromagnetism theory.
Keywords: Ice; Microwave; Atom; Review; Molecule; Crystal; Freezing; Magnetic field; Electric field